2016
DOI: 10.1002/nbm.3626
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of ischemic injury produced by varying severities of photothrombosis differs in neonatal and adult brain

Abstract: Stroke is a major cause of disability in adults and children. Recently, we have developed an adult rat model of minor stroke containing a peri-infarct region with a modest T increase and mild ischemic damage. We hypothesized that a neonatal minor stroke with mild peri-ischemic changes could also be produced, but with potential ontogenic differences. Using our minor photothrombosis method, we produced a range of severities of ischemic lesions (mini, minor, moderate and severe) within magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We used perfusion, diffusion, and T 2 -weighted MRI techniques that are commonly used to characterize ischemic core and estimate penumbra. 1821 To more specifically assess the role of collaterals and exclude confounding reperfusion factors, we used MRI at 1, 5, and 24h after pMCAo. To corroborate the MR findings, we performed cleaved caspase-3 (CC3) and heme oxygenase-1 (HO-1) immunohistochemistry in a subset of animals to quantify ischemic core and penumbra, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We used perfusion, diffusion, and T 2 -weighted MRI techniques that are commonly used to characterize ischemic core and estimate penumbra. 1821 To more specifically assess the role of collaterals and exclude confounding reperfusion factors, we used MRI at 1, 5, and 24h after pMCAo. To corroborate the MR findings, we performed cleaved caspase-3 (CC3) and heme oxygenase-1 (HO-1) immunohistochemistry in a subset of animals to quantify ischemic core and penumbra, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Because the ability to detect brain injury by MRI varies by patient age 13 and time from the sentinel injury, 2 the accuracy of clinical MRI for detecting early and emerging HIE is unclear. Nascent irreversible or reversible neuronal injury, small proportions of selectively vulnerable neurons, and a mix of infarcted and noninfarcted regions soon after HI may raise the complexity of MRI interpretation.…”
mentioning
confidence: 99%
“…Another important consideration revealed in experimental studies of stroke is the changes in BBB permeability from the acute, sub-acute and chronic phases following stroke ictus. Several longitudinal animal studies have shown an 'open-close-open' biphasic pattern in which the BBB has increased permeability at the rst stage, followed by a return to normal values and a second permeability increase [44][45][46]. More recent literature points to a more continuous opening of the BBB with biphasic permeability peaks but without total closing [47][48][49].…”
Section: Discussionmentioning
confidence: 99%